SISTEM PEMELIHARAAN ANJING SEBAGAI SALAH SATU HEWAN PENULAR RABIES PADA PENDERITA RABIES DI PROVINSI BALI TAHUN 2011 - kardiwinata, pasek; Sutarga, Made; subrata, made; Suariyani, Putu (ARCHIVE OF COMMUNITY HEALTH, 2012)
The number of cases of dog bites in the province of Bali has been a rise high enough. 2009, the number of dog bites 21 806 bite, the amount of gain VAR as many as 18 825 people, as many as 27 people died. October 16, 2010 the number of bites as much as 44 629 bites, which get the VAR as many as 38 982 people, as many as 62 people died. According Disnak (2010) maintance system of dog conducted by the Balinese tend to be untied so the dogs are freely to enter and out of the house. An objective to be achieved in this study was to determine the system of dog maintance which is one of the animals transmi! ing rabies (HPR) in patients with rabies in Bali. The study design used was descriptive cross-sectional. The population in this study were all patients who die from the bite of HPR in Bali in 2010-2011, the sample was part of the patient population rabies recorded in Bali Provincial Health O?  ce in 2010-2011 with a porpusive sampling technique People with rabies who had HPR were 35.4%, HPR which were not given VAR about 63.6%, and mostly were detachable cages. The reason of  had dogs were to guard the house and hobbyists. Dogs that bite the sample were not known who were the owner / wild, so a$ er the bite were not known its existence, it is di?  cult to observe, there were also death but were killed only a small part due to illness It showed that the mantaince system of dog were not good. The results of this study can be used as a reference to  the stakeholders in order to prevent disease, especially rabies in dogs and the maintenance system. Future studies on rabies vaccination coverage in dogs and the prevention model in order to reduce the incidence of rabies in the Bali.
Keywords: HPR, Rabies, Bali